1994
DOI: 10.1111/j.1476-5381.1994.tb14823.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of Ca‐activated K channels in red cells by selected dihydropyridine derivatives

Abstract: Thirty two dihydropyridine derivatives were screened as potential inhibitors of the Ca‐activated K‐channel in human red cells. Three derivatives (26, 29, 32 see Tables 1 and 2) with high activity were then characterized in detail, and also tested against the smooth muscle Ca‐channel and shown to have varying potencies. One of the more potent derivatives (32) and nitrendipine were also tested on the Ca‐activated K‐channel, Maxi‐K channel, from mouse pancreatic beta‐cells. We conclude from our results that it ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In C6BU1 cells we have proven KCNN4 expression by using RT‐PCR, shown the functionality of the expressed channel using known channel blocker and have excluded that other than KCNN4 channels mediated Rb + flux by using various reference compounds and toxins. However, some KCNN4 channel‐blocking properties of nitrendipine and related DHP‐derivatives were reported previously (Ellory et al ., 1994). Thus, a weak signal of nitrendipine (IC 50 = 736 ± 148 n m ) was expected.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In C6BU1 cells we have proven KCNN4 expression by using RT‐PCR, shown the functionality of the expressed channel using known channel blocker and have excluded that other than KCNN4 channels mediated Rb + flux by using various reference compounds and toxins. However, some KCNN4 channel‐blocking properties of nitrendipine and related DHP‐derivatives were reported previously (Ellory et al ., 1994). Thus, a weak signal of nitrendipine (IC 50 = 736 ± 148 n m ) was expected.…”
Section: Discussionmentioning
confidence: 74%
“…To clarify whether or not the compounds were also effective on the human target we used human erythrocytes. Previous reports described azoles, other imidazole derivatives and some DHPs as effective KCNN4 blockers on erythrocytes (Gardos channel; Brugnara et al ., 1993a; Ellory et al ., 1994) in vitro and discussed these compounds as a putative pharmacological approach for the therapy of sickle cell disease, which was confirmed in animal models as well as in humans (Brugnara et al ., 1996). As expected, clotrimazole (Brugnara et al ., 1993a) and the triazole blocked A23187‐induced Rb + flux on human erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charybdotoxin (ChTX), a 37-aminoacid toxin, displays a block mechanism similar to maurotoxin, and poor selectivity, blocking effectively other ion channels including KCa1 channels [ 43 ]. Several nonpeptidic molecules have been found to block KCa3.1 channels, such as the vasodilator cetiedil [ 44 , 45 ], the antimycotic triarylmethane clotrimazole (CTL, [ 46 ]), and the antihypertensive L-type Ca 2+ channel blocker nifedipine [ 47 ]. From chemical modification of cetiedil several more potent KCa3.1 channel blockers were obtained.…”
Section: General Properties Of the Kca31 Channelmentioning
confidence: 99%
“…Due to the difficulty in synthesizing phenyl-4H-pyran and its short half-life after intravenous injection ( 62 ), the compound is not a suitable replacement for TRAM-34 as a KCa3.1 inhibitor. Clinically, the antihypertensive drug nitrendipine blocks KCa3.1 channel at a dose of 100 nM ( 65 ). Previous studies have shown that in the PI3K-PI(3)P signaling pathway, LY29400259 (a phosphatidylinositol 3-kinase inhibitor) ( 55 ) and ellagic acid (a nucleoside diphosphate kinase B kinase inhibitor) ( 66 ), prevent phosphorylation of specific group amino acid and inhibit activity of the KCa3.1 channel.…”
Section: Activators and Inhibitors Of Kca31mentioning
confidence: 99%